2015
DOI: 10.1021/ie504312e
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Assisted Ion-Imprinted Cryogels for Selective CdIIIon Removal

Abstract: Herein, we have reported particle-assisted ion-imprinted cryogels, which were synthesized by embedding finely crushed functional particles into cryogel structure under semifrozen conditions. These cryogels showed high adsorption efficiency and affinity against Cd II ions. Cd II adsorption performances were evaluated by varying some effective factors. In order to analyze the data, we applied Langmuir and Freundlich adsorption isotherms while using three different kinetic models, pseudo-first-order, pseudo-secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Tabaklı et al . developed Cd(II)‐imprinted cryogels through particles assisted imprinting approach and reported maximum adsorption capacity as 0.0322 mg/g (32.15 μg/g) cryogel . As a result, the capacity values reported in this study are comparable to or higher than the values reported in literature.…”
Section: Resultssupporting
confidence: 74%
“…Tabaklı et al . developed Cd(II)‐imprinted cryogels through particles assisted imprinting approach and reported maximum adsorption capacity as 0.0322 mg/g (32.15 μg/g) cryogel . As a result, the capacity values reported in this study are comparable to or higher than the values reported in literature.…”
Section: Resultssupporting
confidence: 74%
“…Nevertheless, NIP cryogel was lack of self‐assembled specific binding sites complementary to template ions. The difference in adsorption capacity of MIP and NIP cryogels made this newly synthesized cryogel a promising adsorbent as an important alternative among the traditional materials that possessed high efficiency for removal of metal ions 36 . In comparison to the literature, there were many reports about nickel ion imprinted adsorbents, which emphasized the importance of the removal of nickel ions from aqueous solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in adsorption capacity of MIP and NIP cryogels made this newly synthesized cryogel a promising adsorbent as an important alternative among the traditional materials that possessed high efficiency for removal of metal ions. 36 In comparison to the literature, there were many reports about nickel ion imprinted adsorbents, which emphasized the importance of the removal of nickel ions from aqueous solutions. Among these, Ersöz et al prepared Ni(II) imprinted beads using MAH as the functional monomer and ethyleneglycoldimethacrylate as the cross-linker.…”
Section: The Effect Of Initial Concentrationmentioning
confidence: 99%
“…Later, the Lagergren model was extended to describing the adsorption kinetics of divalent heavy metals by Ho et al, which became the pseudosecond‐order rate equation that is widely used at present. Compared to Lagergren's pseudofirst‐order model, the pseudosecond‐order rate model appears to fit the kinetic data better for a broader range of adsorption systems …”
Section: Introductionmentioning
confidence: 99%
“…Compared to Lagergren's pseudofirst-order model, the pseudosecond-order rate model appears to fit the kinetic data better for a broader range of adsorption systems. [15][16][17] The pseudosecond-order rate model as represented by a semiempirical equation is actually a "lumped" form of more complicated theoretical representations. 18,19 The adsorption rate at a given time is considered to be determined by the difference between the sorption amount (Q t ) at the time and the maximum sorption amount if the system would reach equilibrium (Q e ), that is, (Q e -Q t ).…”
Section: Introductionmentioning
confidence: 99%